POTENSI DAN TANTANGAN ONE BELT ONE ROAD (OBOR) BAGI KEPENTINGAN NASIONAL INDONESIA DI BIDANG MARITIM - Samti Wira Wibawati; Marina Ika Sari; Yuli Ari Sulistyani (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2018)
OBOR is one of the globalization phenomena which causes borderless effect for every country passed by it. OBOR is China’s ambitious connectivity project through infrastructure development and also sea and land transportation route which connect China with Asia, Europe, and Africa. Global connectivity as a goal of OBOR has created opportunities and challenges for Indonesia because it intersects with Indonesia’s national interests. In analyzing the opportunities and challenges of OBOR for Indonesia, the researchers used qualitative method with the concept of national interest and maritime security. The results of this study show that the challenges of OBOR for Indonesia are that OBOR is in line with the Global Maritime Fulcrum related to maritime connectivity and development. On the other hand, OBOR has become a challenge for Indonesia such as in economic sector, in which there are competition between local product and China’s product, and also competition between domestic labors and China’s labors; in defense sector especially in maritime, the challenges are in Malacca Strait, Natuna Islands, South China Sea, and transnational crimes which becomes threats for maritime security.Keywords: Opportunity, Challenge, One Belt One Road, National Interest, MaritimeAbstrakOBOR adalah salah satu bentuk dari fenomena globalisasi yang menciptakan efek borderless bagi setiap negara yang dilaluinya. OBOR merupakan proyek konektivitas ambisius Tiongkok melalui pembangunan infrastruktur dan jalur transportasi darat dan laut yang menghubungkan negaranya dengan kawasan Asia, Eropa, dan Afrika. Konektivitas global sebagai tujuan OBOR telah menciptakan potensi dan tantangan tersendiri bagi Indonesia karena bersinggungan dengan kepentingan nasional. Untuk menganalisis potensi dan tantangan OBOR bagi Indonesia, peneliti menggunakan metode kualitatif dengan konsep kepentingan nasional dan keamanan maritim. Hasil penelitian ini menunjukkan bahwa potensi OBOR bagi Indonesia yaitu OBOR dapat sejalan dengan kebijakan Poros Maritim Dunia terkait dengan konektivitas dan pembangunan infrastruktur maritim. Namun, di sisi lain, OBOR juga menjadi tantangan bagi Indonesia antara lain; di bidang ekonomi yakni persaingan produk lokal dengan produk asal Tiongkok dan tenaga kerja domestik dengan tenaga kerja asal Tiongkok; di bidang pertahanan maritim yaitu di Selat Malaka, Kepulauan Natuna, Laut Tiongkok Selatan, ancaman transnasional crimebagi keamanan maritim. Kata kunci: Potensi, Tantangan, One Belt One Road, Kepentingan Nasional, Maritim